Personal Branding Kader PKB dalam Mendukung Citra PKB Sebagai Partai Terbuka (Inklusif) (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Partai Kebangkitan Bangsa (PKB) is currently recorded as striving to build a new image in Indonesian society as a pluralistic nationalist Islamic party. One of the ways to achieve this is by organizing a collaborative Chinese New Year event, which has been held since 2013 and continues to be implemented regularly to this day. In this case, organizing the celebration at least reflects PKB’s attempt to reshape its image by embracing pluralistic and multicultural principles and values within the national and state context. This study aims to determine the personal branding of PKB cadres in supporting PKB as an open (inclusive) party. The research method used is a descriptive qualitative approach through interviews, observations, and focus group discussions. The result of this study indicate that the personal image of PKB cadres contributes to reinforcing PKB as an open (inclusive) party with membership that is highly accessible to a pluralistic society. In conclusion, it states that the image of PKB cadres contributes to strengthening the party's image as an inclusive entity that embraces all groups in Indonesia. The active involvement of cadres in political communication and social activities such as the Lunar New Year celebration is key to building public trust.